Sociocultural Factors Hindering Public Communication of Positive Body Image in Kazakhstan - Milen Filipov; Adel Askarkyzy; Mehdi Aqarabi (Changing Societies & Personalities)
This research investigated the obstacles hindering the promotion of positive body image among women in Kazakhstan by focusing on sociocultural factors influencing their perceptions. Using a network sampling method, this descriptive study surveyed women aged 18–50 in Almaty and Astana, Kazakhstan’s two largest cities. Participants were recruited through a questionnaire link shared on Instagram by four enablers, which reached 1,000 potential respondents and resulted in 135 returned questionnaires of which 94 were fully completed, thus achieving a 13.5% response rate and a 9.4% completion rate. The study was conducted with a 90% confidence level. The findings indicated that social media, family influence, and the fashion industry were primary obstacles to promoting positive body image in Kazakhstan. While there has been some progress in accepting positive body image in Almaty and Astana, entrenched cultural norms continue to heavily influence perceptions. Young Kazakhstani women often face negative scrutiny if their bodies do not conform to the thin ideal.